Bivalent Histone Modifications By Reiibp Leads to Transcriptional Reprogramming and TLR7-BTK Driven IL-6 Pro-Inflammatory Response in t(4;14) Myelomagenesis - Chong, Shu Yun Phyllis (2021)
ASH Annual Meeting and Exposition